A comprehensive scoping review of tibial cysts after anterior cruciate ligament reconstruction - Nuno Camelo Barbosa; João Pedro Campos; Vânia Capelão; Vikram Kandhari; Thais Dutra Vieira; Bertrand Sonnery‐Cottet (Journal of Experimental Orthopaedics, 2021)
Abstract Purpose The purpose of this study was to perform a scoping review of published literature reporting on surgical management of tibial cysts which developed after ACLR. Methods A scoping review was conducted following the Arksey and O’Malley framework for scoping studies and Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) extension for scoping reviews (PRISMA‐ScR) guidelines. A search strategy using the terms [“Tibial Cyst” AND “ACL”], [“Pretibial Cyst” AND “ACL”] was applied to the PUBMED database. Results Thirty‐seven studies published between 1990 and 2019 were a part of this scoping review. Non‐absorbable implants for tibial graft fixation were used in 10 studies (comprising a total 21 patients), while bio‐absorbable implants were used in 27 studies (comprising a total 115 patients). Incidence of tibial cyst was reported in 3 studies (434 primary ACLRs) from whom 3.9% (n = 17) developed tibial cyst. Tibial cyst development in relation to use of bio‐absorbable screws for tibial ACL graft fixation was reported in 16 studies (42.1%). Use of bio‐absorbable screws with another factor was found to be related to tibial cyst development in another 1 study (2.6%). Most common symptoms were presence of mass or swelling, pain, tenderness, drainage, instability and effusion. Conclusion This scoping review demonstrated that tibial cysts is more frequently related to bioabsorbable screws, however it can also occur due to other causes. Current literature on tibial cyst after ACLR is of low‐quality evidence. Future research is required to better understand aetiology, risk factors for cyst formation and the best possible mode of management. Level of evidence IV